2018
DOI: 10.1177/2043808718787414
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of change in metacognitive and cognitive behavioral therapy for treatment-resistant anxiety

Abstract: Metacognitive therapy (MCT) has shown promising outcomes across disorders, but, currently, little is known about the mechanisms of change in MCT as well as their specificity compared to those of cognitive behavioral therapy (CBT). The main purpose of this study was to examine the within-person relationships between features of the cognitive attentional syndrome (CAS)-the thinking style supposed to maintain clinical disorders according to the MCT model-and anxiety over the course of MCT and CBT for comorbid anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…The model predicts that recovery from depression requires reductions in rumination, worry, and dysfunctional metacognitions, as well as changes in metacognitive beliefs (Wells, 2009). Clarifying the mechanisms of change in MCT may help expand and elaborate understanding of depression and refine the delivery of treatment (Hoffart et al, 2018). Studies should therefore explore if the effects of MCT for depression are related to changes in the hypothesized causal variables.…”
Section: Introductionmentioning
confidence: 99%
“…The model predicts that recovery from depression requires reductions in rumination, worry, and dysfunctional metacognitions, as well as changes in metacognitive beliefs (Wells, 2009). Clarifying the mechanisms of change in MCT may help expand and elaborate understanding of depression and refine the delivery of treatment (Hoffart et al, 2018). Studies should therefore explore if the effects of MCT for depression are related to changes in the hypothesized causal variables.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the disruptive belief of mortality salience is stimulated, and subsequent destructive cycles of detrimental feelings (death anxiety) and negative attitudes and behaviors (ageism), which maintain and exacerbate disruptive beliefs, are activated (Ben-Harush et al 2017 ). These maladaptive dysfunctional cognitive and behavioral responses expressed by nurses caring for older adults can be easily targeted with CBT (Ben-Harush et al 2017 ), as CBT focuses on identifying and changing the function, content, and structure of cognition associated with these dysfunctional behavioral responses (Hoffart et al 2018 ). In a recent study, CBT was shown to help nurses learn alternative methods of thinking or behavior modification (Tanoue et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by our group (Hoffart, Johnson, Nordahl, & Wells, 2018), the latent-trait-state model was adhered to in an examination of a metacognitive model of comorbid anxiety disorders (Wells, 2009). Seventy-four patients who met criteria for a principal disorder of posttraumatic stress disorder (PTSD), SAD, or panic disorder with or without agoraphobia as defined in the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders ( DSM–IV ; APA, 1994) and had failed at least one structured psychological treatment were randomized to 8-week residential metacognitive therapy (MCT) or CBT (see the Supplemental Material available online for details of the sample and treatment).…”
Section: The Latent-trait-state Approachmentioning
confidence: 99%